Konstruksi profesionalisme aparat: Dukungan pimpinan dan perbaikan kesejahteraan - Bintoro Wardiyanto; Dwi Windyastuti Budi Hendrati (Faculty of Social and Political Science, Universitas Airlangga, 2015)
Capacity-building employees has become a global policy instrument in the New Public Management perspective to create the organization's effectiveness and efficiency in the bureaucracy. The release of the State Civil Administrative Law has strengthened efforts to establish the capacity of the officials who are competent and professional. This research uses purposive sampling technique. Respondent were choosen from Food Security Office and Archive and Library Office in 4 areas, namely Bojonegoro, Kapas, Balen, and Dander. In line with the results of the study, it appears that the construction capabilities of the apparatus has a high chance to realize the vision and mission of the new district. In addition, capacitybuilding apparatus in an area determined by the area of leadership role models, the regent than on education leadership. Professionalism apparatus constructed as a positive energy that is not only related to the knowledge and expertise as well as the achievement of an individual's performance, but is highly dependent on the creation of a conducive environment for professionalism itself, such as the feasibility of welfare officials, the clarity of sanctions and rewards as well as encouragement and ethos work.